The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Volume 13: Q (1982)
Reiner, E. (Hg.); Erica Reiner, Editor-in-Charge - Robert D. Biggs, Associate Editor - with the assistance of Maureen Gallery, Brigitte Groneberg, Hermann Hunger, and Burkhart Kienast - Manuscript Editor, Peter T. Daniels; ersch. 1983.